"Safe" and "At-Risk": Cyberbullying Victimization and Deviant Health Risk Behaviors in Youth. Issue 3 (April 2020) - Wood, Frank R.; Graham, Roderick
This study explores the links between cyberbullying victimization and a set of health risk behaviors associated with juvenile delinquency (cigarette smoking, marijuana usage, alcohol usage, and sexual frequency). These links are examined with data from the 2015 Youth Risk Behavior Survey ( n = 9, 122). Using cluster analysis, respondents are categorized into two groups: "safe" students who report on average no engagement in the behaviors measured, and "at-risk" students who report on average moderate to high levels of engagement in sexual frequency, marijuana usage, and alcohol usage. Findings suggest that cyberbullying victimization increases the odds of a student being categorized into the "at-risk" cluster. This effect holds controlling for physical bullying, a proxy measure of self-control, and demographic variables.